ANALISIS SEA LEVEL RISE MENGGUNAKAN DATA SATELIT ALTIMETRI JASON-2 PERIODE 2008-1012 (STUDI KASUS: LAUT UTARA JAWA DAN LAUT SELATAN JAWA) - Yugi Limantara; Bambang Sudarsono; Bandi Sasmito (Jurnal Geodesi UNDIP, 2013)
Sea level changes carried by tidal observations at the beach. But, the method as it still has some shortcomings in some ways such as limited coverage areas around the coast so the sea face of changing data is only accurate for a relatively shallow sea close to the shore. The existence of tidal palm should be tied to the tidal station and measured by GPS in order to be bound by such a reference ellipsoid..Advances in the development of satellite technology, especially satellite altimetry is intended to observe ocean phenomena, has helped many observations of sea level temporally. To see the trend of changes in sea level rise do linear regression. Calculating the regression process SLA and linear trend analysis of the data altimetry satellite Jason 2. In this final project  the results of this regression will be used also to compare the differences in sea level rise in the North Sea Java and South Sea Java. As long years 2008-2012 with satellite altimetry abservations shows that the phenomenon of sea level rise occurred in the North Sea Java and South Sea Java. Sea level rise occurred in the North Sea Java is equal +10.77 mm/yr. Lowest values occurred in Waters Semarang on pass number 64 is equal to +7.92 mm/yr and the highest occurred in the Waters of Madura on pass number 203 is equal to +15.84 mm/yr. For in the sea south of Java, sea level rise is at +16.79 mm/yr. Lowest values occurred in Waters Prigi on pass number 203 is equal to +12.60 mm/yr. As for the sea level rise occurred in the Waters of Cilacap is at +23.04 mm/yr.Keywords: Sea level rise, Altimetry, Sea